Analisis Penolakan Isbat Nikah Perspektif Studi Hukum Kritis - Laili, Rika Nur; Santoso, Lukman (AL-MANHAJ: Jurnal Hukum dan Pranata Sosial Islam, 2021)
This research is based on the problem of isbat nikah request which was rejected by the Ponorogo Religious Court through a determination with case number 402 / Pdt.P /2018/PA.Po. The purpose of this research focuses on the study of the legal interpretation paradigm of judges for rejection of marriage wives which is then analyzed based on the perspective of critical legal studies. This type of research is normative legal research which includes library research with descriptive analysis method. While the data collection technique is a documentation analysis study. The findings of this study: first, the legal interpretation used by the panel of judges in this determination is a systematic interpretation. Meanwhile, the method used by the panel of judges in this case used grammatical interpretation. This can be seen from the basis of legal considerations that the judge rejected the request for marriage is the hadith of the Prophet Muhammad regarding the existence of a marriage guardian as narrated by Ibn Hibban, Article 20 and Article 23 KHI, Article 1 paragraph (2) PMA No. 30 of 2005, Article 2 paragraph ( 1) Law No. 1 of 1974 concerning Marriage. Second, from the perspective of critical legal studies, the panel of judges uses a posivistic paradigm, namely not making any legal breakthroughs. This happens because the law is deemed capable of answering cases, the judge then does not grant marriage requests in order to prioritize the value of legal certainty over the value of justice and the value of benefit. This judge's decision contradicts Gustav Radbruch's standard priority theory, which is the first priority order of justice, second benefit and third legal certainty. Penelitian ini berangkat dari problem permohonan isbat nikah karena menikah siri yang ditolak oleh Pengadilan Agama Ponorogo melalui Penetapan dengan nomor perkara 402/Pdt.P /2018/PA.Po. Tujuan penelitian ini memfokuskan kajian pada paradigma interpretasi hukum hakim atas penolakan isbat nikah yang kemudian dianalisis berdasarkan perspektif studi hukum kritis. Jenis penelitian yang digunakan adalah penelitian hukum normatif yang termasuk studi kepustakaan (library research) dengan metode analisis deskriptif. Sedangkan teknik pengumpulan data adalah studi analisis dokumentasi. Temuan dari penelitian ini: pertama, Interpretasi hukum yang digunakan majelis hakim dalam penetapan ini adalah Interpretasi sistematis. Sedangkan metode yang digunakan majelis hakim dalam perkara ini menggunakan interpretasi gramatikal. Hal ini dapat dilihat dari dasar pertimbangan hukum hakim menolak permohonan isbat nikah adalah hadis Rasulullah tentang harus adanya wali nikah yang diriwayatkan oleh Ibnu Hibban, Pasal 20 dan Pasal 23 KHI, Pasal 1 ayat (2) PMA No 30 Tahun 2005, Pasal 2 ayat (1) UU No 1 Tahun 1974 Tentang Perkawinan. Kedua, Dilihat dari perspektif studi hukum kritis, majelis hakim menggunakan paradigma posivistik yaitu tidak melakukan terobosan hukum. Hal ini terjadi karena undang-undang dianggap telah mampu menjawab kasus, hakim kemudian tidak mengabulkan permohonan isbat nikah demi mendahulukan nilai kepastian hukum daripada nilai keadilan dan nilai kemanfaatan. Keputusan hakim ini berseberangan dengan teori prioritas baku Gustav Radbruch yang dengan urutan prioritas pertama keadilan, kedua manfaat dan ketiga kepastian hukum.